Classic philosophical questions - Gould, James A.; Mulvaney, Robert J. (Pearson/Prentice Hall, 2007)
Classic Philosophic Questions has presented decades of students with the most compelling classic and contemporary primary source readings on the most enduring and abiding questions in philosophy.